Genome-wide identification of NHX (Na+/H+ antiporter) gene family in Cucurbita L. and functional analysis of CmoNHX1 under salt stress - Shen, Changwei; Yuan, Jingping; Li, Xin; Chen, Ruixiang; Li, Daohan; Wang, Fei; Liu, Xing; Li, Xinzheng (Frontiers in Plant Science, 2023)
Soil salinization, which is the accumulation of salt in soil, can have a negative impact on crop growth and development by creating an osmotic stress that can reduce water uptake and cause ion toxicity. The NHX gene family plays an important role in plant response to salt stress by encoding for Na+/H+ antiporters that help regulate the transport of sodium ions across cellular membranes. In this study, we identified 26 NHX genes in three cultivars of Cucurbita L., including 9 Cucurbita moschata NHXs (CmoNHX1-CmoNHX9), 9 Cucurbita maxima NHXs (CmaNHX1-CmaNHX9) and 8 Cucurbita pepo NHXs (CpNHX1-CpNHX8). The evolutionary tree splits the 21 NHX genes into three subfamilies: the endosome (Endo) subfamily, the plasma membrane (PM) subfamily, and the vacuole (Vac) subfamily. All the NHX genes were irregularly distributed throughout the 21 chromosomes. 26 NHXs were examined for conserved motifs and intron-exon organization. These findings suggested that the genes in the same subfamily may have similar functions while genes in other subfamilies may have functional diversity. The circular phylogenetic tree and collinearity analysis of multi-species revealed that Cucurbita L. had a substantially greater homology relationship than Populus trichocarpa and Arabidopsis thaliana in terms of NHX gene homology. We initially examined the cis-acting elements of the 26 NHXs in order to investigate how they responded to salt stress. We discovered that the CmoNHX1, CmaNHX1, CpNHX1, CmoNHX5, CmaNHX5, and CpNHX5 all had numerous ABRE and G-box cis-acting elements that were important to salt stress. Previous transcriptome data showed that in the mesophyll and veins of leaves, many CmoNHXs and CmaNHXs, such as CmoNHX1, responded significantly to salt stress. In addition, we heterologously expressed in A. thaliana plants in order to further confirm the response of CmoNHX1 to salt stress. The findings demonstrated that during salt stress, A. thaliana that had CmoNHX1 heterologously expression was found to have decreased salt tolerance. This study offers important details that will aid in further elucidating the molecular mechanism of NHX under salt stress.